PELATIHAN PENANGANAN CEDERA KEPADA PESERTA DIDIK KELAS V DI MI DARUL HUDA DESA CODO KECAMATAN WAJAK KABUPATEN MALANG - Dio Alief Eka Utama Putra; M. Resa Anggra Kusuma (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2022)
Real Work Lecture (KKN) is one of the courses programmed for Malang State University (UM) Students. In the implementation of the KKN program in Codo Village, the program chosen was